Heart urchins from the depths: Corparva lyrida gen. et sp. nov. (Palaeotropidae), and new records for the southwestern Atlantic Ocean - Flores, Jonathan-N. (2021)
Introduction: Sea urchins in the order Spatangoida are the most diverse group of extant echinoids. Objective: Describe a new genus and species of Spatangoida from abyssal depths, and add new records for known species. Methods: Specimens were collected during several cruises at different areas of the southwestern Atlantic Ocean (SWAO), among 37-55° S latitude at depths ranging from 55 to 3 000 m. We present morphological and ultrastructure analyses. Results: Corparva lyrida gen. et sp. nov. (Palaeotropidae) is described from the Mar del Plata Canyon on the Argentine continental slope (2 950 m depth), the first record of this family from Argentina. Corparva gen. nov. differs in having an apical system semi-ethmolytic, and labrum reaching to rear part of second adjacent ambulacral plate. We also report the northernmost distribution and deepest record for Brisaster moseleyi (38° S latitude, 2 212 m depth), the northward extension of the distribution range of Tripylus excavatus (39° S latitude, 74 m depth), and the first record of Abatus philippii and Abatus agassizii at the Burdwood Bank/MPA Namuncurá. Conclusions: The present work brings novel and updated data about the diversity and distribution of spatangoids from the SWAO, including the description of C. lyrida gen. et sp. nov., and new records of species. This shows how much remains to be known about the diversity and distribution of heart urchins in the SWAO, especially from the deep-sea.